SELECTION AND ORGANIZATION OF MATERIAL FOR ENGLISH PROFESSIONAL COMPETENCE FORMATION IN THE INTERACTION OF FUTURE ADMINISTRATIVE MANAGERS - Медведчук, А. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2018)
The article deals with theoretical research and characterization of criteria for the selection and organization of material for the formation of English professional competence in the spoken interaction of future administrative managers. The peculiarities of the teaching process of English professional spoken interaction of future administrative managers with the consideration of certain criteria for educational material selection are revealed. The notion and content of the term "professionally oriented communicative speaking situation" is clarified. On the basis of the conducted research, the criteria for the selection of educational material were characterized, the unit of selection of educational material was distinguished and a sequential plan for constructing activities for the selection of educational material was provided.